PENGARUH AGAMA TERHADAP KEBAHAGIAAN GENERASI MILENIAL DI INDONESIA DAN SINGAPURA - Mahfud, Choirul; Amalia, Rosa; Putra, Daryl; Tibet, Nafisha; Muqorobin, Hanif; Zabihullah, Fayad; Khoirunnisa, Difa (JURNAL ISLAM NUSANTARA, 2020)
Happiness is not only related to money or wealth, but it can be influenced by religion. This article has a focus and purpose of exploring the views of the Indonesian and Singaporean people regarding the notion of happiness. This article also aims to see how respondents know the understanding of religion, the causes of human hearts that are sad or happy, and know the scientific basis of religion as a path to happiness. Also, to know how to be religious to achieve happiness. Qualitative and quantitative research is the research methods used in this paper—material obtained from guidelines, articles, and survey results. This paper's result is that human life's primary goal is to achieve prosperity and happiness in this world and the hereafter. The achievement of these two main goals must be based on religion because happiness belongs only to Allah. The results showed an influence between Islamic religious activities carried out on the happiness of the millennial generation in Indonesia and Singapore. Humans must uphold religious values to achieve this happiness because religion gives meaning to life. Happiness refers to a healthy heart to relate to Allah SWT as the owner of life. Being close to Him can make a heart calm and happy.